Can sustainable lifestyles bridge the intention–behavior gap in organic food purchasing? A new perspective from the theory of planned behavior - Cuong, Tran; Minh, Dinh Hoang (Journal of Food Technology Research, 2025)
Although scholars have demonstrated a positive relationship between attitude and intention across various fields, the link between intention and behavior has received less attention, especially in the context of sustainable food purchasing. This is understandable, as not all intentions are translated into actual behavior. Recent studies have suggested that examining the moderating effects between intention and behavior is essential to explain why consumers rarely engage in responsible food purchasing behavior. Therefore, this study was conducted to assess the role of sustainable lifestyles (SL) in bridging the gap between intention and behavior in organic food purchasing. Using attitude, a key component of the Theory of Planned Behavior (TPB), as an input variable, data were collected from 773 consumers in Vietnam and analyzed using Structural Equation Modeling (SEM). The findings reveal two key insights: (1) SL significantly helps bridge the gap between intention and behavior in organic food purchasing, and (2) attitude effectively predicts behavior through intention. These results contribute significantly to the existing literature on organic food consumption behavior.